2016
DOI: 10.32404/rean.v3i3.1196
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação De Filmes Biodegradáveis De Proteínas Do Soro De Leite

Abstract: A embalagem tem como função principal manter a integridade do produto, protegendo-o contra danos mecânicos, perda e ganho de umidade. A maior parte das embalagens é fabricada com materiais não biodegradáveis e de fonte não renovável promovendo grande impacto ambiental. Já os filmes biodegradáveis vêm surgindo como alternativa viável a este problema. Os filmes biodegradáveis não apresentam a mesma resistência apresentada pelos filmes sintéticos logo, muitos tratamentos estão sendo aplicados aos filmes na tentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similar data have been reported by Shimazu et al (2007) and Mali et al (2010) who also found that glycerol favours water absorption. Soares et al (2016) recorded variations from 9.20 to 23.79 as a function of storage time and pH concentration, noting that the addition of glycerol increases the absorption of moisture from the environment. Fernandes et al (2015) reported variations in moisture content of between 42.20 and 84.60%, lower than those found here for yam, for films derived from milk whey.…”
Section: Analysis Of Density Solubility Moisture Content Thicknessmentioning
confidence: 99%
“…Similar data have been reported by Shimazu et al (2007) and Mali et al (2010) who also found that glycerol favours water absorption. Soares et al (2016) recorded variations from 9.20 to 23.79 as a function of storage time and pH concentration, noting that the addition of glycerol increases the absorption of moisture from the environment. Fernandes et al (2015) reported variations in moisture content of between 42.20 and 84.60%, lower than those found here for yam, for films derived from milk whey.…”
Section: Analysis Of Density Solubility Moisture Content Thicknessmentioning
confidence: 99%